Flexible, transparent nanocellulose paper-based perovskite solar cells - Lei Gao (Nature Portfolio, 2019)
Transparent perovskite solar cells on paper Modified nanocellulose paper has been shown to be excellent biodegradable substrate for flexible perovskite solar cells and potentially other green flexible devices. A team of Chinese scientists led by Prof Wei Huang from Institute of Advanced Materials, Nanjing Tech University fabricate flexible perovskite solar cells on transparent nanocellulose paper. This becomes feasible only after they develop a treatment recipe to improve the mechanical, optical properties and the waterproof ability of the pure nanocellulose paper. The flexible solar cells on the modified substrates show high specific power of 0.56 W g-1 and good stability and mechanical durability. Another key advantage of nanocellulose paper is its biodegradation capability, making it a better substrate compared to PEN and PET for the next generation green flexible electronics.